CADE: o oligopólio no estado brasileiro de intervenção necessária - Cavalcanti, Rodrigo de Camargo (2014)
The main goal of the present work is to demonstrate that, in an economical structure imminently founded in oligopolies, as the Brazilian one is, it is difficult to ensure the dictates of social justice and to provide a dignified existence to all in face of the legal conduct of the economy, constitutionally implementing a State of Necessary Intervention. With the definition of Economic Rights and its inherent relation to human rights as a starting point, we will draw attention to the Competition Law and look closely to the article 170 of the Federal Constitution, as founding rule of the economic order and resulting antitrust defense model. Furthermore, we emphasise the capitalism as an economic system adopted by the Magna Carta, that establishes an economic order in which profit pursuit is legitimate. Thereafter, we will approach the institutional need of existence of the Administrative Council of Economic Defense (in Portuguese, CADE), contextualizing its inception in the Constitutions of the Brazilian Republic, in the scope of the antitrust defense, indicating some aspects of the Law 8.884/94, as well as the relevant differences to this work as put forth by the Law 12.529/11. To better clarify the question, we show our perspective of two cases of great relevance analysed by CADE, the Ambev and the Nestlé/Garoto cases. Subsequently, we will focus on the theory of concentration acts, identifying its definition according to the recente law of the Brazilian System of Competition Defense (in Protuguese, SBDC) and some of the guidelines given by CADE itself to analyse the acts. We will, then, indicate the negative effects of the concentration acts and and present a proposition to solve them: the harmonisation of the principle of prohibition of social regression with the theory by Ronald Coase of negative externalities, in light of Property Rights in the jurisprudence and German school of thought, which will allow us to bring forth the necessary adoption of new resolving criteria, eminently constitutional. Taking the oligopoly theory as basis, we enfasize the tacit collusion as exemplary unlawfulness of the problems stemmed from the support and consolidation of oligopolistic markets to, at last, discuss the Brazilian stance regarding the antitrust defense towards the international and globalized market. By way of conclusion, we propose some guidelines for SBDC and specifically for CADE, in order to stop oligopolies and follow the dictates of the Brazilian State of Necessary Intervention, as constitutionally provided, that is, an economic order for the dignified existence of all